VASCULAR PATHWAYS OF THE PITUITARY GLAND IN DONKEYS - Al-Dbag, Thamer Abod (The Iraqi Journal of Veterinary Medicine, 1998)
The vascular pathways of the pituitary gland in the donkeys was studied. The contribution of the arterial blood supply of the pituitary gland was described. It was found that the portal vessels of the pituitary gland were originated from the vascular arches, which is found between the pars tuberalis and the infundibulum. These vessels have different extensions and branched in different regions of the anterior lobe of the pituitary gland.